System and load point indices in the power system reliability assessment / Sarina Mohamed Isa - Mohamed Isa, Sarina (2005)
Reliability is the ability of the power system to provide an adequate supply of electrical energy to the customer. The function of a power system is to supply electrical energy on demand, economically and within acceptable levels of reliability and service quality. Power equipment such as generator units and transmission lines are generally considered as the system components. In the life time of their services, these components can be considered in many states such as running, fault repair, planned maintenance and temporary upon the power system reliability. This paper introduces the methodology to evaluate the composite system reliability of generation and transmission system by using the system reliability indices such as expected load curtailed (ELC), expected number of load curtailments (ENLC), expected energy not supplied (EENS), and expected duration of load curtailment (EDLC). These reliability indices are determined based on yearly peak load. The system reliability indices are evaluated on a case study of 3 bus system.